A review of micromachined thermal accelerometers. (16th November 2017) - Mukherjee, Rahul; Basu, Joydeep; Mandal, Pradip; Guha, Prasanta Kumar
Abstract: A thermal convection based micro-electromechanical accelerometer is a relatively new kind of acceleration sensor that does not require a solid proof mass, yielding unique benefits like high shock survival rating, low production cost, and integrability with CMOS integrated circuit technology. This article provides a comprehensive survey of the research, development, and current trends in the field of thermal acceleration sensors, with detailed enumeration on the theory, operation, modeling, and numerical simulation of such devices. Different reported varieties and structures of thermal accelerometers have been reviewed highlighting key design, implementation, and performance aspects. Materials and technologies used for fabrication of such sensors have also been discussed. Further, the advantages and challenges for thermal accelerometers vis-à-vis other prominent accelerometer types have been presented, followed by an overview of associated signal conditioning circuitry and potential applications.